KETERLIBATAN KOMUNITAS: Mengoptimalkan Tempat Pengelolaan Sampah 3R Di Gladak Anyar Pamekasan - Moh. Rizieq Al Kutbi; Mohammad Bustanol Husein; Erina Saputri; Sukron Ma'mun (Halu Oleo University, 2023)
The aim of this research is to determine COMMUNITY INVOLVEMENT: Optimizing the 3R Waste Management Site in Gladak Anyar Pamekasan. This research method uses a qualitative research method, namely by describing the data obtained by analyzing it using indicators of community participation proposed by Peter Oakley, namely based on; : (1) There is contribution, (2) There is organization, (3) Community role and community action, (4) Community motivation, (5) Community responsibility. In collecting data, this research used informant techniques, interview techniques and documentation techniques. Meanwhile, the technique for determining the informants is the Purposive Sampling technique. Purposive Sampling is a technique for sampling data sources with certain considerations. Based on the results of research conducted by researchers, the discussion can be concluded that community participation in the management of the Mitra Gladak Anyar TPS 3R in Gladak Anyar Village, Pamekasan District, Pamekasan Regency is going well with various activities related to waste management as explained above. However, some people also do not have full awareness of sorting their waste, whether organic or non-organic, so sometimes it makes it difficult for waste collectors from TPS 3R to collect it, even to the point of injuring the collector's hand when glass waste is not separated from ordinary waste.